Influence of probiotic feed supplements on functional status of rumen - Luboš Zábranský; Bransilav Galik; Anna Poborska; Veronika Hadačova; Miloslav Šoch; František Lad; Eva Petraškova; Tomaš Frejlach (Journal of Central European Agriculture, 2019)
The aim of this study was to determine how the administration of probiotic feed supplements affects selected parameters rumen environment of cattle, how it impresses the basic chemical and biological processes in the rumen, and also to check their influence on the total digestibility of feed in the cannulated cattle. For the experiment two adult cows of Aberdeen Angus breed with implanted permanent cannula were used, whom probiotics Bifidobacterium sp. were administered daily and subsequently the degradability of the organic matter was determined by the in sacco method. From the samples of rumen fluid, the amount of ammonia, volatile fatty acids, ciliates and pH were analyzed. The impact of probiotics has not been demonstrated in testing the influence of probiotics on the different variables with fixed effect of an individual. When testing the influence of probiotics without the effect of an individual, in the linear model, obtained data of acetic and butyric acid were the best. In their dependence, numbers of protozoa were increasing. However, only two experiment individuals were tested, a strong effect of the individual was found. These results indicate that the effect of probiotics Bifidobacterium sp. on the functional state of the rumen is low.